2020
DOI: 10.1111/hae.14013
|View full text |Cite
|
Sign up to set email alerts
|

Management of comorbidities in haemophilia

Abstract: With the introduction of clotting factor concentrates in the early 1970s, significant improvements in quality of life and life expectancy of persons with haemophilia (PWH) were realized. Unfortunately, as a result of transmission of HIV and hepatitis C virus (HCV) by contaminated concentrates in the 1980s, many of these gains were lost. Now with four decades of PWH unexposed to contaminated factor products and current treatments capable of suppressing and eliminating HIV and HCV, respectively, the survival rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 75 publications
(82 reference statements)
1
24
0
7
Order By: Relevance
“…A number of studies have reported the increasing life expectancy of patients with haemophilia with comorbidities, 1 and we recently reported on the situation in Japan. 2 Although thrombotic diseases are expected to increase in these populations, balancing treatment to prevent bleeding and thrombosis in patients with haemophilia is very challenging.…”
Section: Successful Emicizumab Prophylaxis During Dual Antiplatelet Therapy For Insertion Of Drug-eluting Stents After Acute Coronary Synmentioning
confidence: 95%
“…A number of studies have reported the increasing life expectancy of patients with haemophilia with comorbidities, 1 and we recently reported on the situation in Japan. 2 Although thrombotic diseases are expected to increase in these populations, balancing treatment to prevent bleeding and thrombosis in patients with haemophilia is very challenging.…”
Section: Successful Emicizumab Prophylaxis During Dual Antiplatelet Therapy For Insertion Of Drug-eluting Stents After Acute Coronary Synmentioning
confidence: 95%
“…Desafortunadamente, la era de los concentrados de plasma para el tratamiento de la hemofilia sufrió un gran revés, debido a la transmisión del virus de la inmunodeficiencia humana (VIH) y de la hepatitis C (VHC), a través de los concentrados de factores de coagulación fabricados a partir de plasma de múltiples donantes [30,33]. Miles de pacientes con hemofilia fallecieron por complicaciones del VIH/SIDA en los 80 y 90.…”
Section: Evolución Histórica Del Tratamientounclassified
“…Como resultado del progreso en la terapia para la hemofilia, la esperanza de vida de los pacientes se ha equiparado a la de la población general [35,36]. Esto ha llevado al desarrollo de enfermedades crónicas asociadas a la edad, previamente no vistas en la población con hemofilia, como trastornos cardiovasculares y osteoporosis [33,35].…”
Section: Evolución Histórica Del Tratamientounclassified
“…Now with the widespread availability of replacement therapy to prevent and treat active bleeding, improved management of blood-borne infections through surveillance, and effective treatment options for hepatitis C and HIV, affected individuals can expect a normal life span [6]. The change in the age distribution for persons with hemophilia (PwH) has led to the recognition of other comorbidities related to hemophilia [7,8]. A large and growing body of literature has revealed an increased prevalence of skeletal fragility in both children and adults with hemophilia.…”
Section: Introductionmentioning
confidence: 99%